Virtual Actuator Design for Uncertain Metzler Systems - Krokavec, Dušan; Filasová, Anna (Frontiers in Control Engineering, 2021)
The paper presents the design conditions adequate in design of virtual actuators and utilisable by nominal static output control structures in fault-tolerant control for strictly Metzler systems. The positive stabilisation with Hinf norm performance is also addressed for virtual actuator design for strictly Metzler systems with interval uncertainty matrix representations of single actuator faults. Taking into account disturbance conditions and changes of values of variables after the virtual actuator activation, the design conditions are outlined in the terms of linear matrix inequalities. The approach provides a way to obtain acceptable dynamics of the closed loop system after virtual actuator activation.